Menjajaki Potensi Islamisasi Ilmu Ekonomi - Qosim, Nanang (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
Science is not value-free. It is a product of culture and civilization. Historically, Economics is one of the sciences originating from Western civilization that has values that not only cause civilization that has values that not only lead to the prosperity of society but also destroy and oppress society but also at the same time destroys and oppresses them. In addition, the science of economics has created human beings who only achieve the luxury of the world and forget the life after death. forget about life after death. The purpose of writing this article is to introduce the worldview of Islam toward the sciences, especially economics and of the sciences, especially economics, and attempt to Islamize it. trying to Islamize it. The method of this research is by reading various literature, analyzing and connect the relationship. The result is that Islamization of economics is very important and urgent to direct humans to the right goals in life. directing humans to the right goals in life. With the Islamic worldview, the happiness of life in the world and the hereafter will be achieved. world and the afterlife.